Cobalt catalyzed sp3 C–H amination utilizing aryl azides. Issue 11 (30th July 2015) - Villanueva, Omar; Weldy, Nina Mace; Blakey, Simon B.; MacBeth, Cora E.
Abstract : A dinuclear Co(ii ) complex supported by a modular, tunable redox-active ligand system is capable of selective C–H amination to form indolines from aryl azides in good yields at low (1 mol%) catalyst loading. Abstract : A dinuclear Co(ii ) complex supported by a modular, tunable redox-active ligand system is capable of selective C–H amination to form indolines from aryl azides in good yields at low (1 mol%) catalyst loading. The reaction is tolerant of medicinally relevant heterocycles, such as pyridine and indole, and can be used to form 5-, 6-, and 7-membered rings. The synthetic versatility obtained using low loadings of an earth abundant transition metal complex represents a significant advance in catalytic C–H amination technology.